Constitutively expressed c-myb abrogates the requirement for insulinlike growth factor 1 in 3T3 fibroblasts. - Travali, S (1991)
The proto-oncogene c-myb, whose expression is usually limited to cells of the hematopoietic lineages, can be expressed in fibroblasts if placed under the control of a constitutive promoter, such as the simian virus SV40 early promoter. 3T3 cells carrying a constitutively expressed human c-myb were found to grow in 1% serum or in a serum-free, platelet-derived growth factor-supplemented medium, whereas the parent cell line, BALB/c 3T3, needed insulinlike growth factor 1 (IGF-1) in addition to platelet-derived growth factor for growth. myb-carrying cells, however, could not grow in platelet-poor plasma. In fibroblasts, therefore, a constitutively expressed c-myb can abrogate the requirement for platelet-poor plasma or IGF-1. When 3T3 cells constitutively expressed both c-myc and c-myb, they could grow in serum-free medium without added growth factors. The ability of c-myb to abrogate in fibroblasts the IGF-1 requirement seems to be due to its ability to induce overexpression of IGF-1, as indicated by an increase in steady-state levels of IGF-1 mRNA. These results have some important implications; for instance, they suggest a commonality of pathways for entry into S phase in different cell types and the possibility of a myb-like or myb-equivalent gene product of critical importance for entry of fibroblasts into S phase.